Continuous dynamic adjustment of the plant circadian oscillator - Alex A. R. Webb (Nature Portfolio, 2019)
Biological circadian rhythms maintain a period close to 24 h in coordination with the Earth’s fixed rotational period. Here Webb et al. discuss how external cues continuously adjust phase and period, viewing the oscillator as a dynamically-adjusted plastic system rather than tightly-coupled cogs in a mechanical clock.